Long-term outcome 10 years or more after restorative proctocolectomy and ileal pouch-anal anastomosis in patients with ulcerative colitis - Leowardi-Bauer, Christine; Hinz, Ulf; Tariverdian, Mirjam; Kienle, Peter; Herfarth, Christian; Ulrich, Alexis; Kadmon, Martina (Langenbeck's archives of surgery, 2010)
Purpose: The aim of this study was to assess quality of life (QOL) in a long-term follow-up of patients with ulcerative colitis (UC) 10 years and more after ileal pouch–anal anastomosis (IPAA) to correlate these results with pouch function and to assess the long-term pouch failure rate. Methods: In a unicentric study, 294 consecutive patients after IPAA between 1988 and 1996 were identified from a prospective database. QOL was evaluated according to the validated Gastrointestinal Quality of Life Index (GIQLI). Results: Overall median follow-up was 11.5 years. Thirty-seven patients experienced pouch failure (12.6%). The rates of ileal pouch success after 5, 10 and 15 years were 92.3%, 88.7% and 84.5%. According to the GIQLI, patients with a functioning pouch achieved a mean score of 107.8, reflecting a decrease of QOL of 10.8% compared to a healthy population. There were significant negative correlations between QOL and an age of >50 years (p < 0.05), pouchitis, perianal inflammation and increased stool frequency (p < 0.0001). Conclusions: QOL and functional results of patients with UC 10 years or more after IPAA were acceptable; however, those were reduced when compared to a healthy population. Pouch failure rate still increases up to 15.5% 15 years after IPAA. This result represents an important issue in providing patients with comprehensive preoperative information.
Online veröffentlicht: 12. März 2009
Gesehen am 13.03.2023